2007
DOI: 10.1063/1.2757098
|View full text |Cite|
|
Sign up to set email alerts
|

Broadband dielectric spectroscopy on single-crystalline and ceramic CaCu3Ti4O12

Abstract: We present dielectric measurements of the colossal dielectric constant material CaCu 3 Ti 4 O 12 extending up to 1.3 GHz also covering so far only rarely investigated single crystalline samples. Special emphasis is put on the second relaxation reported in several works on polycrystals, which we detect also in single crystals. For polycrystalline samples we provide a recipe to achieve values of the dielectric constant as high as in single crystals.Among the vast number of papers on the extremely high ("colossal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
121
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 21 publications
9
121
0
Order By: Relevance
“…Therefore, it is concluded that the existing long-range ferroelectric order in these Te doped samples is broken due to quantum fluctuations below 167 K. In pure CCTO, the TiO 6 octahedra show unusual tilting of 23 • (a + a + a + ) in Im3 cubic symmetry. 19 The Glazer tilt angle of BO 6 octahedra in tetragonal I4/mmm symmetry is calculated to be 24.6 • (a 0 b + b + ) for CCTTO samples. 15 As the octahedral tilt angle is larger for Te doped samples as compared to that of pure CCTO, one could expect high displacive polarizability from "rattling" cation (Ti 4+ and Te 4+ ) in octahedral cage arising from locally stretched lattice for Te-doped samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is concluded that the existing long-range ferroelectric order in these Te doped samples is broken due to quantum fluctuations below 167 K. In pure CCTO, the TiO 6 octahedra show unusual tilting of 23 • (a + a + a + ) in Im3 cubic symmetry. 19 The Glazer tilt angle of BO 6 octahedra in tetragonal I4/mmm symmetry is calculated to be 24.6 • (a 0 b + b + ) for CCTTO samples. 15 As the octahedral tilt angle is larger for Te doped samples as compared to that of pure CCTO, one could expect high displacive polarizability from "rattling" cation (Ti 4+ and Te 4+ ) in octahedral cage arising from locally stretched lattice for Te-doped samples.…”
Section: Resultsmentioning
confidence: 99%
“…Dielectric behaviour of doped samples confirms polarization increase with a decrease in temperature (limited range) which is very similar to the anomalous dielectric behaviour of incipient ferroelectric or ferroelectric perovskite oxides in the low temperature region (0-250 K). The dielectric behaviour of the incipient ferroelectrics at low-temperatures can be fitted according to the Barrett's equation as given below; 18,19 …”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] For CCTO ceramics, spectroscopic plots of the real component of the capacitance (C9) near room temperature (RT) exhibit a frequency-independent plateau over the range y10-10 5 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…The larger relaxor-like mode 2 most likely is of MW type, arising from a so-called surface-barrier layer capacitor (SBLC) at the sample surface [18,30]. The missing ' peak for this relaxation indicates similar conductance of the SBLC and the bulk [29].…”
mentioning
confidence: 99%